Estimation of Above-Ground Carbon-Stocks for Urban Greeneries in Arid Areas: Case Study for Doha and FIFA World Cup Qatar 2022 - Habib, Salma; Al-Ghamdi, Sami G. (Frontiers in Environmental Science, 2021)
Urban areas are significant sources of anthropogenic carbon dioxide (CO2), which elevates air pollution. However, urban greenery has a positive effect on mitigating air pollution and the impact of CO2 on the climate. Quantifying the benefits of greenery for urban environments involves complex calculations and requires significant resources. Such a quantifying exercise is not cost-effective. The satellite remote sensing method can analyze current and near-present carbon-stock dynamics through spectral band imaging. In this research study, field measurements determine above-ground carbon (AGC) stock. The field measurements are derived from three types of land use, comprising public parks and gardens, institutional parks, and street and avenue greenery in selected locations in Doha city in Qatar. These field measurements are then correlated with results from satellite images. Linear and non-linear regression models are established between AGC and five vegetative spectral indices (VIs) derived from the Landsat 8 Operational Land Imager (OLI). The AGC stock for the selected locations in Doha in 2014 is evaluated using the highest coefficient of determination with the highest accuracy expected. The results of the analysis reveal that both the normalized difference vegetation index (NDVI) (R2 = 0.64) and the relative ratio vegetation index (R2 = 0.71) significantly correlate with the AGC in public parks. In avenue vegetation, all the VIs exhibit high R2, but the best fit is NDVI (R2 = 0.87). The CO2 equivalent range evaluated from the AGC in the plots studied in Doha is measured as 650.6 tons for the period between 2014 and 2020, with an annual sequestration rate of 108.4 tons per year. This CO2 equivalent storage amount has the social value of USD 35,788, which is the equivalent of QR 131,341. The AGC-VI correlation in land-use groups may be influenced by the turf grass and impervious surfaces in the background of the images. Further study of urban landscapes and vegetation with high biomass is likely to show its positive effects for cities and that it can improve carbon dioxide abatement. This improvement in CO2 abatement in Qatar can be useful for various environmental estimations for the World Cup 2022.